0008 Effect of drug take back events in lehigh county, pa. (26th April 2015) - Synnamon, David
Abstract : Statement of purpose: The City of Allentown and surrounding municipalities in Lehigh County have participated in the DEA's National Take Back Day drug collection event held bi-annually since 2010. These events have been increasingly successful as measured by greater amounts of drugs collected and a decrease in poisoning hospitalizations in Lehigh County. Methods/Approach: The Allentown Health Bureau, the Lehigh County DA and local and state police officers choose sites throughout the county for drug collection events. The dates and times are advertised by the organisations staffing the sites. The sites accept drugs to be disposed of including capsules, pills and liquids. Residents who dispose of medications may remain anonymous. Results: There have been nine drug take back events in Lehigh County since 2010. These events have resulted in the collection of 8, 145 pounds of medication. From 2010 to 2012, hospitalizations due to poisoning in Lehigh County fluctuated between 10.5%–12.5% of all injuries in Lehigh County. However, in 2013, poisonings dropped to 9.5% of all hospitalised injuries in Lehigh County, with approximately 160 fewer poisonings than the previous year. This is the lowest percent of injuries due to poisonings since the start of data availability in 1997 and the lowest number of hospitalised poisonings in Lehigh County since 2001. Conclusions: The Lehigh County drug take back events are not only successful in their stated goal of collecting unused and unwanted medications from county residents, but the drop in the amount of hospitalizations due to poisonings will hopefully develop into a trend. Hospitalizations should be tracked closely over the next several years to see if this decrease can be sustained and research should be conducted to see if it can be attributed to a lack of access to prescription drugs. Significance and contribution to the field: The Lehigh County drug take back events have shown themselves to be effective examples of public health social marketing because they promote the voluntary behaviour of their target audience by offering benefits individuals want and removing barriers to participation.